الانزياح الأسلوبي في القرآن الكريم - بديوي، أنس (جامعة البعث, 2013)
يشتغل البحث على مصطلح نقدي، برز في الدراسات النقدية الحديثة والمعاصرة، هو الانزياح. ويشكل مفارقته باختيار النص القرآني حقلا تطبيقيا، وبالوقوف على ظاهرة أسلوبية، ومعالجتها من منظور نظرية التلقي، معتمدا مقولة محوريه فيها، هي كسر أفق توقع القارئ. \ ولعل المشكلة الرئيسة في إعداد البحث ناجمة عن تداخل حقوله المعرفية المختلفة، من نقدية ونحوية ولغوية ودينية؛ مما استدعى مقدمات نظرية، بدا فيها شيء من التطويل، شدا وجذبا إلى نقطة رئيسة، يتمحور حولها النقاش. \ ويبدو أن وضوح الناظم المعرفي الذي حدد مسوغات البحث وأهدافه، نأى بنا عن الخلط والشطط وعدم وضوح الرؤية والمنهج، في أثناء التطبيق. فقد عمق البحث مقولته النظرية تمكينا للبعد التطبيقي، وهو الأساس الذي تقوم عليه الدراسة، ولا سيما أن خصوصية القرآن الكريم تستدعي خصوصية في الطرح والمعالجة. \ واستجلى البحث أهمية الوقوف على الظاهرة الأسلوبية في تعميق فهم النص القرآني، لغويا وأسلوبيا، وأوضح إمكان الإفادة من مقولات بعض الاتجاهات النقدية المعاصرة، في قراءة النص القرآني، وتلقيه، بأبعاده الدلالية، رؤية وتأويلا. This research works on a critical term called " deviation" which emerged in the recent and modern critical studies. It differently chooses the Koranic text as an applying field to consider and deal with this stylistic phenomenon from the viewpoint of receptive theory, adopting a pivotal statement namely, "breaking the horizon of the reader's anticipation". \ The main problem in preparing this research may come from the overlapping of its different epistemic fields such as criticism, syntax, language and religion. This required theoretical expanded introductions to lead to a main point on which the \ discussion pivoted. \ The clarity of the epistemic organizer, which defined the justifications of the research and its goals seems to take us away from mix, excess and lack of visibility and methodology during application. \ The research deepened its theoretical statement to confirm the applying dimension which is the base on which the study is made, especially as the characteristic of the Holy Koran requires a characteristic in expounding and dealing. \ The research showed the importance of considering the stylistic phenomenon in deepening the understanding of the Koranic text linguistically and stylistically. It also showed the possibility of benefiting from the statements of some modern critical trends in reading the Koranic text and receiving it with its indicative dimensions visibly and interpretively
Keywords: القرآن الكريم -- الأسلوب -- الانزياح -- بلاغة القرآن